(untitled) (Web of Teachers: Inderscience Research, 2026)
This exploratory mixed-method study examines how mood (Uzbek kayfiyat) is conceptualized and linguistically encoded in the Baburnama and how Uzbek EFL learners attempt to preserve mood when translating between Uzbek and English. Drawing on a small set of ko‘ngil-based phraseological items and their renderings in three major English translations (Leyden & Erskine, 1826; Beveridge, 1921; Thackston, 1996), the study identifies recurring translation shifts: (1) locus relocation (ko‘ngil/heart to mind), (2) metaphor restructuring (motion/impact to weather imagery or dispositional predication), and (3) explicitation (affective settling to cognitive adequacy).